2019
DOI: 10.3389/fpls.2019.00615
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Events Occurring During Softening of Strawberry Fruit

Abstract: Changes in fruit texture taking place during ripening, described as softening, are mainly due to alterations in structure and/or composition of the cell wall. Several non-covalent interactions between the three carbohydrate polymers of the cell wall, cellulose, pectins and hemicellulose, and many structural proteins and ions, enable a complex structure. During softening, the disassembly of the cell wall structure takes place, mediated by a complete set of cell wall degrading enzymes or proteins. Softening is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
97
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 90 publications
2
97
0
2
Order By: Relevance
“…Furthermore, the N-terminus sequence alignment of FaRALF1-1, FaRALF3-1, FaRALF7-1, FaRALF8-1a and FaRALF13 peptides with AtRALF23 (Fig 4A) shows that residues directly involved in AtRALF23 binding with AtLLG2 are conserved, suggesting that FaRALF peptides in strawberry fruits may also interact with the Fxa LLG2 homolog and Fxa FER Malectin Like Receptor Kinase (MRLK) to a heterotypic complex. Consistently, the homology models of FaRALF3-1 peptide interaction with FaMRLK47 - the MRLK mostly expressed in Fxa fruits [50] and with the Fxa LLG2 homolog (maker-Fvb3-4-snap-gene-34.65), shows that the structural components necessary to bind MRLK47 and LLG2 are conserved in FaRALF3 (Fig 4B and C), suggesting a similar binding mechanism and complex formation. In Arabidopsis, At RALF23 binding to FERONIA and LLG proteins leads to negative immunity response regulation, however further analyses will be required to test FaRALF3-1 effectiveness binding to MRLK47 in fruits.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…Furthermore, the N-terminus sequence alignment of FaRALF1-1, FaRALF3-1, FaRALF7-1, FaRALF8-1a and FaRALF13 peptides with AtRALF23 (Fig 4A) shows that residues directly involved in AtRALF23 binding with AtLLG2 are conserved, suggesting that FaRALF peptides in strawberry fruits may also interact with the Fxa LLG2 homolog and Fxa FER Malectin Like Receptor Kinase (MRLK) to a heterotypic complex. Consistently, the homology models of FaRALF3-1 peptide interaction with FaMRLK47 - the MRLK mostly expressed in Fxa fruits [50] and with the Fxa LLG2 homolog (maker-Fvb3-4-snap-gene-34.65), shows that the structural components necessary to bind MRLK47 and LLG2 are conserved in FaRALF3 (Fig 4B and C), suggesting a similar binding mechanism and complex formation. In Arabidopsis, At RALF23 binding to FERONIA and LLG proteins leads to negative immunity response regulation, however further analyses will be required to test FaRALF3-1 effectiveness binding to MRLK47 in fruits.…”
Section: Resultssupporting
confidence: 65%
“…In a recent work, Jia et al [50] analyzed the expression of the woodland strawberry ( F. vesca ) Malectin Receptor Like Kinases (MRLK) also known as the Catharanthus roseus RLK-like proteins (CrRLK1Ls). F. vesca MRLKs are encoded by more than 60 genes, and more than 50% of these are expressed during fruit development.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethylene plays a key role in the development of strawberry color, in the accumulation of taste-related compounds (flavonoids, phenolics, organic acids, and sugars), and in the softening process (Villarreal et al, 2010;Merchante et al, 2013;Li et al, 2016a;Villareal et al, 2016;Moya-León et al, 2019). Moreover, it has been reported that ethylene biosynthesis and signaling genes are differentially expressed during ripening of strawberry, and that some Ethylene Response Factors (ERFs) showed an expression pattern similar to those found in a climacteric fruit (Trainotti et al, 2005;Sun et al, 2013;Sánchez-Sevilla et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The high perishability of strawberry represents a bottleneck for expanding the fresh market supply chain (Terry et al, 2011). Strawberry is classified as a non-climacteric fruit and its ripening is mainly regulated by the abscisic acid (ABA)/auxins ratio (Moya-León et al, 2019). In particular, auxins have been associated with ripening inhibition, while ABA accumulation has been linked with promotion of strawberry fruit ripening (Jia et al, 2011;Symons et al, 2012;Leng et al, 2014;Chen et al, 2015;Chen et al, 2016;Giné-Bordonaba and Terry, 2016;Jia et al, 2016;Li et al, 2016b;Medina-Puche et al, 2016).…”
Section: Introductionmentioning
confidence: 99%